Error Analysis and Interlanguage: Reflections for Indonesian Teachers and Learners - Rindu Handayani (Jurnal Bahasa dan Sastra, 2017)
Abstract: This paper aimed to describe the role of error analysis and interlanguage as a natural process in teaching and learning. Extensive history of English learning in Indonesia is described in the paper as it gives a view of how English has been used for decades. The terms of error and interlanguage by Corder and Selinker are also elaborated briefly. Errors occur due to two interferences:  interlingual and intralingual. Clear intruments of students’ performance towards English competence, feedbacks of teachers and students in language learning engagement, and a fruitful advantage for teachers and learners for their further reseource of learning are some points that have been proposed for Indonesian teachers and learners. Keywords: Error analysis, interlanguage, language teaching in Indonesia Abstrak: Makalah ini bertujuan untuk menggambarkan peran analisis kesalahan dan interlanguag sebagai proses alami dalam proses belajar dan mengajar. Sejarah yang panjang pembelajaran di Indonesia juga dijelaskan dalam makalah ini karena memberikan pandangan tentang bagaimana bahasa Inggris digunakan selama beberapa waktu. Ketentuan kesalahan dan antar bahasa oleh Corder dan Selinker juga diuraikan secara singkat. Kesalahan terjadi karena dua gangguan: interlingual dan intralingual. Instrumen yang jelas dari kinerja siswa terhadap kompetensi bahasa Inggris, feedback dari guru dan siswa dalam keterlibatan pembelajaran bahasa, dan beberapa keuntungan yang bermanfaat bagi guru dan peserta didik sebagai sumber belajar mereka berikutnya adalah beberapa poin yang telah ditulis untuk guru dan pelajar bahasa Inggris di Indonesia. Kata-kata kunci : analisis kesalahan berbahasa, interlanguage, pembelajaran Bahasa Inggris di Indonesia